2020
DOI: 10.1177/1049732320960050
|View full text |Cite
|
Sign up to set email alerts
|

Grounded in Culture: Reflections on Sitting Outside the Circle in Community-Based Research With Indigenous Men

Abstract: Research continues to be a dirty word for many Indigenous people. Community-based participatory research (CBPR) is a means to disrupt power dynamics by engaging community members within the research process. However, the majority of relationships between researcher and participants within CBPR are structured within Western research paradigms and they often reproduce imbalances of power. The purpose of this article is to reflect on the process of CBPR within a research project focused on Indigenous men’s mascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Practically, this meant that, in some cases, R1 as the non-Māori researcher and doctoral student “gave way” to the relationship already established between the R2 and the participant—The interview was led and conducted primarily by R2, with R2 there to assist and contribute when appropriate. This ability to “sit outside the circle,” as articulated by Waddell and colleagues (2020) , allowed for a more engaged interview encounter, with the prioritization of participants rather than researchers. This required an acknowledgment and negotiation of the cultural (Pākehā and Māori) and other power dynamics (PhD student, and undergraduate student and tutor, respectively) between the two researchers, as well as a certain degree of humility ( Krusz et al, 2020 ; Waddell et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, this meant that, in some cases, R1 as the non-Māori researcher and doctoral student “gave way” to the relationship already established between the R2 and the participant—The interview was led and conducted primarily by R2, with R2 there to assist and contribute when appropriate. This ability to “sit outside the circle,” as articulated by Waddell and colleagues (2020) , allowed for a more engaged interview encounter, with the prioritization of participants rather than researchers. This required an acknowledgment and negotiation of the cultural (Pākehā and Māori) and other power dynamics (PhD student, and undergraduate student and tutor, respectively) between the two researchers, as well as a certain degree of humility ( Krusz et al, 2020 ; Waddell et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This ability to “sit outside the circle,” as articulated by Waddell and colleagues (2020) , allowed for a more engaged interview encounter, with the prioritization of participants rather than researchers. This required an acknowledgment and negotiation of the cultural (Pākehā and Māori) and other power dynamics (PhD student, and undergraduate student and tutor, respectively) between the two researchers, as well as a certain degree of humility ( Krusz et al, 2020 ; Waddell et al, 2020 ). This was an instinctive, dynamic process which evolved as the interview progressed and involved a constant negotiation of the multiple and subtle ways in which we were both insiders and outsiders to participants, as Indigenous and non-Indigenous, as women, parents, and students, and as people with varying backgrounds and life experiences ( L. T. Smith, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…This “method of discovering relations,” evident in the sewing sessions, reflects the centrality of relationships to the lives of many Indigenous Peoples ( Wilson, 2008 , p. 84), including Inuit. Relational, storytelling methodologies, then, such as sharing circles ( Waddell et al, 2020 ) or the use of yarning in interviews ( Byrne et al, 2021 ), are often used in Indigenous research contexts. The voicing of stories, described in the results, can also be situated within the decolonizing “project of storytelling,” wherein Smith (2012) states that “intrinsic in story telling is a focus on dialogue and conversations amongst ourselves as indigenous peoples, to ourselves and for ourselves” (p. 146).…”
Section: Discussion: Sewing As Facilitative Of Data Gatheringmentioning
confidence: 99%
“…This was soon expanded to include any setting, particularly literature from high-income countries that describes community engagement or participatory research with Indigenous communities, as this literature often explicitly grapples with histories of harm inflicted through research. 19 21 After thorough and iterative discussions about the review aim and objectives, two articles identified through initial, evolving searches and reading were selected (‘berrypicking’ 58 ) to elicit the initial theories. 44 The rationale for selection was to allow a consideration of both beneficial and harmful engagement, and relevance for NCDs, even if not explicitly describing NCD research or interventions.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 44 The rationale for selection was to allow a consideration of both beneficial and harmful engagement, and relevance for NCDs, even if not explicitly describing NCD research or interventions. 19 20 A list of initial theories was first elicited through abductive thinking and retroductive theorising (see table 1 ). 45 This meant considering the outcomes of research and interventions described in the two selected studies, and "working backwards to think about the conditions of reality that are necessary for such effects to manifest".…”
Section: Methods and Analysismentioning
confidence: 99%